The Effect of Brand Image and Electronic Word of Mouth (E-Wom) on Buying Interest of Mixue Consumers in Generation Z in Surabaya City - Syakban, Medi Hendika; Dermawan, Rizky (International Journal of Economics (IJEC), 2025)
This study aims to analyse the effect of brand image and electronic word-of-mouth (e-WOM) on the purchase intention of Mixue consumers in Generation Z in Surabaya City, using a quantitative approach. The research population comprises Mixue consumers in Generation Z in Surabaya City. The sample consists of 100 Mixue consumer respondents born between 1997 and 2012 and domiciled in Surabaya City, selected using the accidental sampling technique. The data were analysed using descriptive statistics and partial least squares (PLS) with the SmartPLS application. The results demonstrated that brand image has a positive and significant effect on purchase intention. Similarly, e-WOM was found to have a positive and significant effect on purchase intention.